2005
DOI: 10.1007/bf02724412
|View full text |Cite
|
Sign up to set email alerts
|

Urinary calcium to creatinin ratio in children

Abstract: Due to difficulty of 24hr urine collection in children for detection of hypercalciura, random urine calcium to creatinin ratio (U Ca/Cr) has been used for screening hypercalciuria. The purpose of this study was to determine normal U Ca/Cr ratio in primary school age children in North of Iran. This study was performed on 590 healthy school-age children, aged between 7-11 years. Early morning random urine samples from all children were analyzed for calcium and creatinine. Mean value and 95th percentile for U Ca/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
8
1
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 16 publications
5
8
1
1
Order By: Relevance
“…So the present study was conducted to establish a reference interval in our study area and it was first found that there was a significant inverse relationship between urinary Ca/Cr ratio and age. This finding was well corroborated with several previous studies [9,16,[19][20][21][22]. It also observed that for every age group, different urine Ca/Cr ratio was reported [3,8,23].…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…So the present study was conducted to establish a reference interval in our study area and it was first found that there was a significant inverse relationship between urinary Ca/Cr ratio and age. This finding was well corroborated with several previous studies [9,16,[19][20][21][22]. It also observed that for every age group, different urine Ca/Cr ratio was reported [3,8,23].…”
Section: Resultssupporting
confidence: 92%
“…As for most analytes, the lower and upper reference limits are assumed to demarcate the estimated 2.5 th and 97.5 th percentiles respectively, of the underlying distribution of values [24], percentile values of urinary Ca/Cr ratio were calculated. 95 th and 97.5 th percentile for urinary Ca/Cr ratio of different age groups in present study in this geographic area was the same as some reports and different with other [1,6,9,10,[14][15][18][19][20][21][22][23][25][26][27][28][29]. Then upper reference value of urinary Ca/Cr ratio of different age group were found and this to some extent different from one previous study [11].…”
Section: Resultssupporting
confidence: 61%
See 1 more Smart Citation
“…In Chinese children, the predominantly vegetarian diet containing higher oxalate and lower calcium may be the reason for the relatively high rate of whewellite stones, especially in older children with eating habits more similar to adults' than younger children. Weddellite stones are related to high urinary excretion of calcium, which decreases with age in children [11,12]. Thus, weddellite stones occurred more often in younger children.…”
Section: Discussionmentioning
confidence: 97%
“…Hiperkalsiüri ve taş olgularında aile öyküsünde %40 oranında ürolitiyaz öyküsü vardır. 31,[81][82][83][84] İyi bir diyet öyküsü alınmalıdır. Hastanın sıvı ve tuz tü-ketimi, C vitamini veya D vitamini desteği, özel diyet (ketojenik diyet gibi) alıp almadığı sorgulanmalıdır.…”
Section: Nütrisyonel Nedenlerunclassified